The 2011 round of the international comparison programme (ICP) in Latin America and the Caribbean (UN ECLAC SantiagoCL)
Outlines the objectives and background of the International Comparison Programme (ICP) in Latin America and the Caribbean, whose purpose is to collect price data for goods and services for different countries using a comparable consumer basket and to estimate the relevant purchasing power parities (PPPs).
Keywords: STATISTICAL SERVICES